KITAB ADABUL ‘ALIM WAL MUT’ALLIM THE WORK OF K.H. HASYIM ASY'ARI IN THE DEVELOPMENT OF MODERN ISLAMIC EDUCATION - Charisma Jalil Indranata; Dzulkifli Hadi Imawan (Universitas Muhammadiyah Surakarta, 2022)
The focus of research is how the values of moral education contained in the book Adabul'Alim wal Muta'allim fima Yahtaju ilaih al-Muta'allim in KH Hasyim Asy'ari 's thinking in the world of modern Islamic education and also how the role of the book Adabul'Alim wal Muta'allim fima Yahtaju ilaih al-Muta'allim in the development of modern Islamic education in Indonesia. This type of research is a literature study. Primary sources and data come from the book Adabul'Alim wal Muta'allim fima Yahtaju ilaih al-Muta'allim. The results of the first research on moral education in the book Adabul'Alim wal Muta'allim fima Yahtaju ilaih al-Muta'allimt consist of 8 chapters which can be classified into 3 important parts, namely the significance of education, the responsibilities and duties of students, and the responsibilities and duties of the teacher. Two roles of the book Adabul'Alim wal Muta'allim fima Yahtaju ilaih al-Muta'allim in building the development of modern Islamic education civilization in Indonesia which focuses on intelligence and intellectuals with noble moral values.